Long-term prognostic value of microvascular obstruction by cardiac magnetic resonance in ST-segment elevation myocardial infarction - Raquel P. Amier; Casper W. H. Beijnink; José F. Rodriguez Palomares; Martijn W. Smulders; Gonzalo Pizarro Sánchez; Rodrigo Fernández-Jiménez; Filipa X. Valente; Albert C. van Rossum; Niels van Royen; Borja Ibañez; Robin Nijveldt (PLoS ONE, 2026)
Aims Microvascular obstruction (MVO) portends a higher risk of remodelling and adverse events following ST-segment elevation myocardial infarction (STEMI). However, data regarding the implications of MVO in STEMI beyond five years of follow-up are scarce. Methods & Results This is a pooled analysis of three observational studies including 876 prospectively enrolled reperfused first STEMI patients, who underwent cardiac magnetic resonance imaging with late gadolinium enhancement (LGE), between 2003–2019. Median follow-up duration was 6.3 (IQR 3.6–9.3) years. The primary outcome was all-cause mortality. The secondary outcome was a combined endpoint of all-cause mortality and recurrent ischemic events (i.e., myocardial infarction or stroke). We performed Cox regression analyses with a time-dependent covariate. The study population consisted of 876 patients, mean age 59 years ± 12, 720 men (82%). MVO was present in 499 patients (58%). The presence of MVO was independently associated with all-cause mortality up to six years post-STEMI (Hazard Ratio [HR] 2.23, 95% CI 1.09–4.57, p = 0.029), but not after six years post-STEMI (HR 0.98, 95% CI 0.45–2.12, p = 0.958). Presence of MVO was not significantly associated with a combined endpoint of all-cause mortality and recurrent ischemic events before or after six years of follow-up (HR 1.27, 95% CI 0.81–1.99, p = 0.294 and HR 0.68, 95% CI 0.35–1.31, p = 0.244, respectively). Conclusions In STEMI patients, the presence of MVO by cardiac magnetic resonance imaging is associated with a more than two-fold higher risk of all-cause mortality up to six years after the index event. This relation seems to dissipate beyond this time period.